Biocompatibilitity evaluation of fetal scalp monitoring spiral electrode using high resolution scanning electron microscope - Farid, Che Ghazali (Pusat Pengajian Sains Perubatan, 2013)
Perinatal fetal heart monitoring involves the placement of a scalp electrode to detect the fetal electrocardiogram. The spiral scalp electrode is one type of cardiac monitor, which requires the distal end of the monitor to be screwed into the infant's scalp. The goal of fetal heart monitoring was to identify "abnormal" fetal heart patterns so that timely intervention (expedited birth) might lower rates of perinatal morbidity and mortality resulting from asphyxia. Although this involves inserting an electrode through the dilated cervix and attaching the electrode to the scalp of the fetus, it can lead to bacterial infection caused by invasive fetal scalp electrode monitoring. Objective: - To examine and assess the post inserted fetal scalp electrode surface microbiologically and with high resolution scanning electron microscope - To detect possible remnants and contamination of resterilized post inserted fetal scalp electrode with soft tissues, microorganisms and plague using VPSEM observations. - To examine and assess the characteristics changes of post inserted fetal scalp electroe surface using VPSEM as an alternative and prompt diagnostic tool to study the relationship of fetal scalp electrode clinical complications (bacteria, pain etc). - To examine and assess if VPSEM will reveal the basic structure of fetal scalp electrode and manufacturer's biocompatibility defects of post insertion fetal scalp electrode - To test the hypothesis that the fetal scalp electrodes used in HUSM have various degree of trauma accountability related to their manufactured morphology or adherence to the related human anatomy.